2018
DOI: 10.1103/physrevlett.121.190502
|View full text |Cite
|
Sign up to set email alerts
|

Secure Quantum Key Distribution over 421 km of Optical Fiber

Abstract: We present a quantum key distribution system with a 2.5 GHz repetition rate using a threestate time-bin protocol combined with a one-decoy approach. Taking advantage of superconducting single-photon detectors optimized for quantum key distribution and ultra low-loss fiber, we can distribute secret keys at a maximum distance of 421 km and obtain secret key rates of 6.5 bps over 405 km.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
389
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 608 publications
(393 citation statements)
references
References 24 publications
(27 reference statements)
2
389
1
1
Order By: Relevance
“…The fluctuations of the relative permittivity of the atmospheric air can be statistically modeled [24][25][26][27][28][29][30][31][32]. The probability distribution of the parameters in equation (2) can then be analytically estimated, as shown in [21,22]. A brief recap of the derivation and the main results is presented in appendix A.…”
Section: Free-space Optical Links and The Elliptic Beam Approximationmentioning
confidence: 99%
“…The fluctuations of the relative permittivity of the atmospheric air can be statistically modeled [24][25][26][27][28][29][30][31][32]. The probability distribution of the parameters in equation (2) can then be analytically estimated, as shown in [21,22]. A brief recap of the derivation and the main results is presented in appendix A.…”
Section: Free-space Optical Links and The Elliptic Beam Approximationmentioning
confidence: 99%
“…We also observe that the protocol seems to be quite robust against intensity fluctuations of the optical pulses prepared by the parties.The last few decades have witnessed major advancements in the field of quantum communication [1, 2], with quantum key distribution (QKD) [3-13] being its most developed application. Recent experiments over about 400 km of optical fibers [14,15] and over about 1000 km of satellite-to-ground links [16,17] demonstrated that QKD over long distances is possible. Despite such remarkable experimental achievements, the private capacity of point-to-point QKD is intrinsically limited by fundamental bounds [18,19].…”
mentioning
confidence: 99%
“…We also note that, although the results are calculated in the absence of device imperfections, the calculations of error rate for the X-basis for the weak coherent state are close to ones obtained experimentally in [26] with real device imperfections. With currently available state-of-the-art device performance (see [27]), the results would be even more representative of the actual error rates. Therefore, we expect that the results for the amplitude-squeezed coherent state obtained here represent a potential improvement over the weak coherent state.…”
Section: Resultsmentioning
confidence: 99%
“…In practice however, weak coherent source (attenuated laser) is often used instead, due to limitations of single photon source for QKD applications. Indeed, recently a record maximum distance of 421 km for fiber-based QKD with state-of-the-art device performance employing laser source has been reported [27]. Therefore, the analysis of multi-photon interference is important in a MDI-QKD setup for calibration purpose, and for predicting coincidence probability using other states, such as the squeezed coherent state.…”
mentioning
confidence: 99%